P66 Taking nudge digital with food choice at work: from evaluation to practical application in everyday workplace settings. (3rd September 2019) - Fitzgerald, S; Geaney, F; Perry, IJ
Abstract : Background: Evidence on effective workplace dietary interventions is limited. The Food Choice at Work trial assessed the comparative effectiveness of a workplace dietary intervention involving nutrition education and system-level dietary modification both alone and in combination versus a control workplace on employees' dietary intakes, nutrition knowledge and health status. An economic evaluation assessed the cost-effectiveness of the interventions from the perspective of healthcare providers in terms of QALYs and employers in terms of monetary benefits (reduced absenteeism). Methods: Four manufacturing workplaces in Ireland were allocated to control, nutrition education (Education), system-level dietary modification (System-level) and nutrition education and system-level dietary modification (Combined). Nutrition education included group presentations, individual consultations and detailed nutrition information. System-level dietary modification included menu modification, fruit price discounts, strategic positioning of healthier alternatives and portion size control. Data on dietary intakes, nutrition knowledge, health status, QALYs and absenteeism were obtained at baseline and at 7–9 months follow-up. Multivariate analysis of covariance compared changes across the groups. The economic evaluation included cost-utility and cost-benefit analyses. Results: Follow-up data were obtained for 541 employees (18–64 years) (64% of 850 recruited). There were significant positive changes in intakes of saturated fat (p=0.013), salt (p=0.010) and nutrition knowledge (p=0.034) between baseline and follow-up in the combined intervention versus the control. Significant changes in BMI (− 1.2 kg/m2 (p=0.047) were also observed in the combined intervention. System-level modification yielded the highest additional QALYs (€101.37/QALY) and annual net benefit for employers (€56.56/employee). Discussion: Combining nutrition education and system-level dietary modification is an effective approach for promoting healthy eating at work. The FCW intervention is a sustainable cost-effective model and wide-scale implementation is underway at local, national and international workplaces. Specific elements will be digitally automated to increase the reach of the FCW intervention. The purpose of our next related study is to develop, implement and assess the effectiveness of digitalising the FCW intervention. The results of this study will determine the effectiveness and user engagement of a theory-based, multidimensional, web platform and smartphone nutrition intervention to support healthier food choices and better health status for employees in their workplaces.